Patrocinia of St. Barbara in the Diocese (Archdiocese) of Warmia - Andrzej Kopiczko (Saeculum Christianum)
The cult of St. Barbara in the Warmian diocese dates back to the activities of the Teutonic Order. Its earliest traces can be linked to 1242 and the fortress in Sartowice near Świecie, where the saint‘s relic was kept. Subsequently, chapels dedicated to her were established in Bratian, Gdańsk, Königsberg, and Malbork. In the diocese of Warmia within its pre-1992 boundaries, churches bearing her name were found in Boguchwały, Kętrzyn, Krzyżanowo, Rogóż (first), Pasym, Ryn Reszelski, Srokowo, Straszewo, Sztum, and Turów. Currently, in the Archdiocese of Warmia, only these churches in Boguchwały, Rogóż, Ryn Reszelski, and Kętrzyn remain. Many religious buildings have been equipped with sculptures of St. Barbara in their altars (usually alongside St. Catherine) and to a lesser extent, with paintings. There were also fraternities dedicated to her in Nowy Staw, Pasłęk, and Nidzica, but at the beginning of the 20th century they remained only in Tolkmicko. Although the cult of St. Barbara in the Warmian archdiocese is no longer popular (except in Boguchwały and Rogóż), historically it played a significant role, similar to other female saints: Anne, Elizabeth, Catherine, Margaret, and Mary Magdalene.